Characterization of the complete mitochondrial genome of Coelastrum_sp.F187 - Zhao Kai Wang; Li Juan He; Fan Hu; Xiang Zhi Lin (Mitochondrial DNA. Part B. Resources, 2017)
Coelastrum is a genus of green algae that belongs to the Scenedesmaceae family. There is little information available about this genus. A phylogenetic analysis of the ITS2 sequences showed that Coelastrum is a paraphyletic group. To better explore the phylogenetic status of this genus, we report the mitochondrial genome sequence of Coelastrum sp. F187 using next-generation sequencing technology. The complete mitochondrial genome is 52,888 bp in size and encodes 43 conventional mitochondrial genes, including 14 protein-coding genes (PCGs), 24 transfer RNA (tRNA) genes, and four ribosomal RNA (rRNA) genes. Most of the PCGs (12/14) and all tRNAs were located in the heavy chain and the light chain, respectively. The phylogenetic analysis based on the complete mitochondrial genome sequences indicated that Coelastrum is closely related to Pectinodesmus pectinatus. The sequenced complete mitochondrial genome of Coelastrum sp. F187 provides fundamental molecular data that will be useful for species identification, population genetics, and evolutionary relationships.